Temporal order of atrial fibrillation and acute myocardial infarction and associated prognosis in the Danish Diet, Cancer and Health cohort - Emelia J Benjamin; Anja Olsen; Henrik Kjaerulf Jensen; Christina C Dahm; Tanja Charlotte Frederiksen; Morten Krogh Christiansen (Open Heart)
Background Atrial fibrillation (AF) and acute myocardial infarction (AMI) share risk factors and are bidirectionally associated. Several studies found higher risks of outcomes in individuals with both conditions. Whether the risks of outcomes differ according to temporal order of AF and AMI is unclear.Methods The study was based on the Danish Diet, Cancer and Health cohort. We assessed the risk of heart failure (HF), ischaemic stroke (IS) and all-cause mortality during 10 years of follow-up in participants with both AF and AMI compared with only one and according to the temporal order of AF and AMI in participants with both conditions.Results We identified 5816 participants with newly diagnosed AF only, 3448 with first AMI only, 348 with AF before AMI and 721 participants with AMI before AF. The multivariable-adjusted risks of HF, IS and all-cause mortality were higher among participants with both AF and AMI compared with participants with only AF or AMI. In participants with both, there was no difference in risk of HF (HR 0.92, 95% CI 0.72 to 1.17) or IS (HR 1.12, 95% CI 0.76 to 1.66) between participants with AF before AMI compared with AMI before AF. AMI before AF was associated with lower all-cause mortality compared with AF before AMI (HR 0.70, 95% CI 0.54 to 0.90).Conclusions Risks of adverse outcomes were higher among participants with both AF and AMI compared with only AF or AMI. All-cause mortality, but not risk of HF or IS, differed according to temporal order with a lower mortality among participants with AMI before AF.